Przyszli nauczyciele wobec hipotetycznych epizodów przemocy rówieśniczej wśród uczniów - Tłuściak-Deliowska, Aleksandra (Studia Edukacyjne, 2018)
Substantive preparation but also the beliefs and attitudes of prospective professionals to important social issues are essential for their later work in the education sector. One such important social and educational problems is peer violence at school. The article presents the results of a study aimed at understanding the attitudes of students of Pedagogy (teaching specialization, N = 267) toward bullying in schools, its different types and ways of coping with it. The episodes (vignette) method was used in the study. Based on the data obtained, it can be stated that in preparing prospective teachers, particular attention must be paid to relational (hidden) violence and verbal violence. Further findingsand implications are formulated in the text.